COLLABORATIVE GOVERNANCE: SYNERGY OF ENVIRONMENTAL AGENCY AND BPBD IN FLOOD MITIGATION IN KRIAN DISTRICT - Muslimin; Mustofah , Amirul; Haryati , Eny; Devy Pramudiana, Ika (International Journal of Multidisciplinary Reseach, 2025)
This research analyzes the synergy between the Environmental Office (DLH) and the Regional Disaster Management Agency (BPBD) in flood mitigation in Krian District, Sidoarjo, through Collaborative Governance. Krian faces annual flood risks due to land-use changes and high sedimentation. Methodologically, this study employs a qualitative descriptive approach with a case study design. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles, Huberman, and Saldana interactive model. The findings indicate that collaboration has successfully transformed inter-institutional relationships into a synergistic ecosystem. Trust-building and data transparency have minimized